Judgment calls : twelve stories of big decisions and the teams that got them - Davenport, Thomas H.; Manville, Brook (Boston, Mass. : Harvard Business Review Press, 2012)
Your guide to making better decisions despite the dizzying amount of data at our disposal today$1 (Band an increasing reliance on analytics to make the majority of our decisions$1 (Bmany of our most critical choices still come down to human judgment. This fact is fundamental to organizations whose leaders must often make crucial decisions: to do this they need the best available insights.In Judgment Calls, authors Tom Davenport and Brook Manville share twelve stories of organizations that have successfully tapped their data assets, diverse perspectives, and deep knowledge to build an organizational decision-making capability$1 (Ba competence they say can make the difference between success and failure. This book introduces a model that taps the collective judgment of an organization so that the right decisions are made, and the entire organization profits. Through the stories in Judgment Calls, the authors$1 (Bboth of them seasoned management thinkers and advisers$1 (Bmake the case for the wisdom of organizations and suggest ways to use it to best advantage. Each chapter tells a unique story of one dilemma and its ultimate resolution, bringing into high relief one key to the power of collective judgment. Individually, these stories inspire and instruct; together, they form a model for building an organizational capacity for broadly based, knowledge-intensive decision making. You$1 (Bve read The Wisdom of Crowds and Competing on Analytics. Now read Judgment Calls. You, and your organization, will make better decisions.s
Keywords: Decision making; Problem solving